(untitled) (Agroindustria, Sociedad y Ambiente, 2026)
Plant species have been used since ancient times as part of traditional medicine due to their different biological properties. The research was carried out with the aim of characterising the phytochemical and functional components of the muyuyo flower (Cordia lutea Lam) by applying different drying temperatures. A completely randomised experimental design was used, evaluating the incidence of three drying temperatures (T1: 40°C; T2: 50°C and 60°C). The drying kinetics were determined as a function of time and temperature applied, to subsequently evaluate the presence of phytochemical components, antioxidants and antimicrobial activity of the extracts. The results with the ethanolic extract at 40 °C showed the highest antioxidant capacity with values of 2944.68 µmol TE/g (ABTS) and 5036.03 µmol TE/g (DPPH), which was significant according to Tukey’s test (p<0.05). In contrast, the aqueous extracts showed the highest total phenol contents (88–94 mg GAE/g). Phytochemical screening showed a higher presence of tannins, flavonoids, catechins, saponins, and free amino acids, which play important biological roles in the body. Antimicrobial activity was most effective in 100% ethanol extracts, with inhibition halos ranging from 9.33 to 11.33 mm. It was concluded that the muyuyo flower has biological potential for use in industries such as pharmaceuticals and food.